Permethrin chronic exposure alters motor coordination in rats: Effect of calcium supplementation and amlodipine - Godinho, A. F. [UNESP]; Stanzani, S. L. [UNESP]; Ferreira, F. C. [UNESP]; Braga, T. C. [UNESP]; Silva, M. C. [UNESP]; Chaguri, J. L. [UNESP]; Dias-Junior, C. A. [UNESP] (Elsevier B.V., 2014)
Recently was observed that pyrethroids decrease motor coordination and that calcium channels can be important targets for this effect. To contribute with this observation, this work studied the motor coordination and exploration (using hole-board apparatus), and locomotion (using open-field apparatus) of rats exposed to following treatments: permethrin (PM), PM plus calcium gluconate (CG) and PM plus amlodipine (AML). The results obtained show that CG or AML alone not changed the motor coordination while PM decreases it. CG kept the effect of permethrin; AML, however, decreased the values of permethrin to the control. Locomotor activity and exploration, which could confound results of motor coordination, were not modified by treatments. The concentration of PM in brain tissue was increased by the CG and AML. The neurosomatic index (weight brain/body weight) was increased by the PM and PM + CG. In conclusion, the combined results here obtained indicates that the calcium ion and the channels in which it is involved can be important targets for the toxic effect of pyrethroid insecticide permethrin on motor nerve activity of rats. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Permethrin; Motor coordination; Calcium; Behavior; Amlodipine; Rat